Structural, optical, and electrical properties of V2O5 thin films: Nitrogen implantation and the role of different substrates - Priya, Bhanu; Jasrotia, Priya; Kumar, Arun; Singh, Vinamrita; Jire L. Hmar, Jehova; Kumar, Raj; Kulriya, Pawan Kumar; Kumar, Tanuj (Frontiers in Materials, 2022)
In this work, we report the effect of substrate and nitrogen (16 keV N+) ion implantation on the structural, morphological, compositional, and electrical properties of V2O5 thin films, grown by thermal evaporation on various substrates, including glass, Si, and sapphire (named as V2O5:Gl, V2O5:Si, V2O5:Sp, respectively). Structural analysis showed the formation of the mixed (α, and β-V2O5) phases on all substrates but the β-V2O5 phase is highly dominating in case of the V2O5:G and V2O5:Si samples. A deformation in β-phase of V2O5 thin films under ion implantation-induced strain results in the change of crystallite size. Irradiation suppresses XRD peaks in relative intensities, indicating partial amorphization of the film with defects formation. The micro-structural analysis confirmed the formation of the uniform-sized nanorods for V2O5:Si, whereas isolated crystallites were formed for other types of substrates. Thermal conductivity may influence the size and shapes of V2O5 crystallite forms on different surfaces. Silicon absorbs heat more effectively than sapphire or glass results in nanorods formation. A decrease in optical bandgap and electrical conduction has been observed due to increase in oxygen vacancies, induced electron scattering and trapping centres on N+ implantation. Thus, the present study offers a unique advantage of simultaneous reduction in optical band-gap and conductance of V2O5 thin films which is important for the optoelectronic applications.